Determinants of Environmental, Social, and Governance (ESG) in the Indonesian Mining Industry - Musaev Tulkin; Mimin Widaningsih; Indah Fitriani (Akuisisi : Jurnal Akuntansi, 2026)
This study aims to analyze the influence of company size, profitability, and leverage on the Environmental, Social, and Governance (ESG) performance of mining companies listed on the Indonesia Stock Exchange for the 2020–2024 period. The study uses a quantitative approach with panel data from seven mining companies. ESG performance is measured based on ESG scores from sustainability reports and related databases, while company size is proxied by the natural logarithm of total assets, profitability using Return on Assets (ROA), and leverage is calculated through the ratio of total debt to total assets. Analysis was conducted using multiple linear regression to examine the relationship between financial characteristics and ESG performance. The results show that company size and profitability have a positive and significant effect on ESG performance, indicating that companies with larger scale and better financial condition tend to have stronger sustainability practices. Conversely, leverage has a negative and significant effect, indicating that high debt levels can limit companies in implementing sustainability initiatives. This study concludes that the ESG performance of mining companies in Indonesia is influenced by the company's internal financial strength and capital structure.